Pengaruh campuran perekat dan waktu penekanan terhadap karakteristik briket cangkang biji karet - Dwi Irawan; Mafruddin; Ardiyanto Darmanto (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Biomass is organic material derived from living things that can be converted into fuel through biological and thermochemical processes. The thermochemical conversion of biomass is divided into several direct combustion processes, pyrolysis/carbonization and gasification. Briquettes are produced from pyrolysis by converting biomass into charcoal which is then formed into solid fuel. The aim of the study was to determine the effect of the adhesive mixture and pressing time on the proximation value and burning of briquettes. Raw material for rubber seed shells with variations of molasses adhesive 70% : 30%, 75% : 25%, and 80% : 20%, also variations in pressing time of 30, 45, and 60 minutes using the hot stamping method with a temperature of 120oC and a pressure of 200 bar. The results showed the best calorific value, a mixture of 80% : 20%, pressing time of 60 minutes, namely 5,903.19 cal/g, while the water content, and the ash content is still above the SNI for household briquettes. Combustion time for a mixture of 80% : 20% takes 30 minutes to reach a temperature of 1000C, an average of 35 minutes.